The Effect of World Oil Price on Türkiye’s Exchange Rate - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2023)
Oil prices are used in international markets both as one of the key prices and as an indicator price for other energy sources other than oil. Especially in developing oil importing countries like Turkey, the relationship of this important input with the exchange rate has always been an interesting research topic. In this study, the relationship between oil prices and nominal exchange rate in Turkey is examined by causality tests using daily data set (total 5168 observations) for the period of 3 April 2013-3 April 2023. The findings obtained from the analyzes indicate the existence of a unilateral causality relationship between the variables. This positive relationship indicates that there is a causality running from oil prices to the exchange rate. On the other hand, there was no causal relationship from exchange rate to oil prices. The results obtained show similar results with such articles made before in the literature.